Developing heat mitigation wall by integrating PCM into building material - Umi Nadiah Nor Ali; Norazman Mohamad Nor; Alil Eizlan Mohd Shah DJohan; Azrul Affandhi Musthaffa (Penerbit Universiti Kebangsaan Malaysia, 2021)
Population growth and industrial demand are related in construction of buildings and houses which contribute to increment of energy consumption. The invention of phase change materials (PCMs) with high latent heat capacity were explored to be integrated into building materials. PCMs are substances that are capable of storing large amounts of thermal energy as latent heat during their phase transition. Development of this product can ensure a comfortable indoor temperature in buildings without depending on air conditioning system which consumes more energy and damage the environment not to mention contributing towards global climate change. This research concentrated on proposing the method of PCM incorporation and its heat resistance performance. Calcium Chloride Hexahydrate (CaCl2.6H2O) was used in this research while the incorporation method is direct mixing into gloss paint and added into zip-lock plastic then covered by conventional cement plaster. From the data obtained, we can see the PCM incorporated wall is better in heat resistance than wall without PCM resulting difference in temperature between internal and external wall 3 ˚C rather than 1 ˚C. For the conclusion , PCM incorporated wall can decrease the internal temperature of building slightly contributing to conserving nature by reducing air conditioner system consumption.